CONTEMPORARY TRENDS IN STUDIES ON MOBILE LEARNING OF FOREIGN LANGUAGES: A META-ANALYSIS. - Giusi Antonia Toto; Pierpaolo Limone (International Journal of Engineering Education, 2019)
Previous research has provided a review of the literature on the state of research on mobile learning, but the use of m-learning and MALL to formal and informal learning of foreign languages needs further study. The need to review the language learning assisted by mobile devices emerges from a globalized context, in which pedagogy must question itself to plan and design research drawings in which mobile learning assumes a fundamental importance in teaching practice aimed above all at new generations of students.This study adopts a meta-analysis approach to systematically review the literature, thus providing a more complete analysis and synthesis of 83 studies from 2009 to 2018. Previous studies focus on the effectiveness and design of the mobile learning system.The search for databases and citations was performed by limiting the keywords referring to m-learning and to MALL. Compared to existing reviews, the results confirm revealing a skill-based approach to language learning with an emphasis on vocabulary, learning factors that influence students' perceptions and availability to use new cellular technologies.